2010
DOI: 10.1080/15289168.2010.510986
|View full text |Cite
|
Sign up to set email alerts
|

Making Meaning Together: Helping Survivors of Violence to Learn at School

Abstract: The deleterious effects on cognitive capacity in children and adolescents who have been exposed to violence at home and in the community have been meticulously documented. What is less well known is how very much these youngsters want to learn at school. Children and adolescents from violent backgrounds, like others, equate education with a hopeful future and are eager to attend. However, when they do go to school, the violence that they experience leaves them terrified to think. Instead they resort to concret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Perry (1997, 2002, 2009) has documented the impacts of trauma on brain development and cognition, finding that children who have been victimized suffer developmental arrests. Bragin (2005; Bragin & Bragin, 2010) has developed school and community‐based programs that remediate some of these cognitive delays and arrests through school and community‐based programs.…”
Section: A Community Psychoanalytic Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Perry (1997, 2002, 2009) has documented the impacts of trauma on brain development and cognition, finding that children who have been victimized suffer developmental arrests. Bragin (2005; Bragin & Bragin, 2010) has developed school and community‐based programs that remediate some of these cognitive delays and arrests through school and community‐based programs.…”
Section: A Community Psychoanalytic Frameworkmentioning
confidence: 99%
“…Studies have also shown that violence can impact brain development and interfere with the development of containment, communication, and coping skills (Bragin, 2005, 2009; Bragin & Bragin, 2010; Fonagy et al., 2017; Howell, 2020; Lyons‐Ruth, 2002; Lyons‐Ruth & Jacobovitz, 2008; Lyons‐Ruth et al., 2003; Perry, 2002, 2009; Twemlow et al., 2001; Yasik et al., 2007). Because safety at a neurobiological level involves the activity of the vagal pathways—those stimulated by social engagement—fostering a responsive and empathic community is crucial to creating the conditions for optimal learning (Porges & Dana, 2018).…”
Section: A Community Psychoanalytic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such difficulties can be mitigated through the promotion of activities that build the protective factors mentioned earlier, such as participating in familiar cultural (or classroom) routines, the belief that they are able to affect their surroundings, and that they are good and valuable members of their (classroom) community. Opportunities to do something good, and affect their community in a positive way, can make children feel profoundly better (Bragin & Bragin, ). Children who find themselves unable to connect, or who sulk in the corner isolating themselves from others, can be given activities that help the teacher, a schoolmate, or the community at large.…”
Section: Specific Psychological Difficulties That Make It Hard For Chmentioning
confidence: 99%
“…Data from research studies conducted in different schools ( Bragin & Bragin, 2010 ; Slade, 2007 ; Twemlow, Fonagy, & Sacco, 2005 ) has shown that the competence of mentalization is a supportive learning tool, because it serves as a scaffolding function in student learning ( Freda, Esposito, Martino, & González-Monteagudo, 2014 ; Padykula & Horwitz, 2012 ). In contrast, there are only a few studies that investigate mentalizing competence in an academic context with a non-psychotherapeutic perspective.…”
Section: Introductionmentioning
confidence: 99%